Indigenous fishing gears in Suraha Lake, Ballia, Uttar Pradesh, India - Srivastava, PK; Srivastava, SJ (Journal of Wetlands Ecology, 2011)
The study aimed at assessing the indigenous fishing methods adopted by the fishermen in Suraha Lake. Survey was conducted during August 2002 - July 2004. Information was collected through participatory rapid appraisal covering the entire lake and four fishermen villages viz Mairitar, Surajpura, Kaithauli and Basantpur. Study indicated that various types of local indigenous traditional fishing gears are used by fishers for commercial exploitation of the lake. Plank-built boats (Dingi) were used in the fishing. These boats are small and light and prepared locally by fishers. Gill net and cast net were the main gears and contributed more then 80% of the total fish catch of the lake. Indigenous fishing gears comprising gill nets, cast nets, traps, etc., have been discussed showing their modus operandi. Key words: Indigenous fishing methods; suraha lake DOI: http://dx.doi.org/10.3126/jowe.v5i0.5156 J Wet Eco 2011 (5): 73-78